In vitro antibacterial and synergistic activity of pyrazolyl sulphonamide derivatives against Staphylococcus haemolyticus - Yahaya, Ewura Seidu; Anak, Jesse Azebiik; Amissah, Nana Ama; Obuah, Collins; Agyei, Phyllis Elsie Owusu; Saahene, Roland Osei; Ainooson, Michael; Ablordey, Anthony; Ekor, Martins (Creative Pharma Assent, 2024)
Background: Antimicrobial resistance has rendered several anti-infective agents ineffective, necessitating the need to intensify efforts to identify and develop novel drugs against microbial infection. Structural modification of existing antibiotics continues to be one of the areas of intense research focus in recent times. Objective: This study assessed the antibacterial and synergistic activity of fifteen pyrazolyl sulphonamide derivatives in Staphylococcus haemolyticus. Methods: Antibacterial activity was determined using the broth microdilution method. The ability of test compounds to interact with tetracycline was assessed using the checkerboard synergy testing method and the Loewe synergy and antagonism model. Results: Seven compounds (46.6%) were significantly active against the bacteria (MIC 1 µg/mL – 16 µg/mL), and four were confirmed to form synergistic combinations with tetracycline in checkerboard and Loewe analysis. Conclusion: Observations from this study has demonstrated the antibacterial activity and the synergistic potential of the novel pyrazolyl sulphonamides with tetracycline, highlighting the possible role of modified sulphonamides as a rich resource for antimicrobial development.